Team Games-Language Learning Model in Improving Students’ Speaking and Listening Skills Viewed from Creativity - Kenza Tacarraoucht; Kufakunesu Zano; Alex Zamorano (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
Speaking and listening are language skills that are supporting each other. Students who have good speaking competence will have good listening skills as well. Unfortunately, students who have good listening skills do not indicate that they have good speaking skills. To help students in improving speaking and listening, this study applied team games-based language learning (TG-BLL) model. This model was designed with appropriate learning materials and activities, and English experts validated the quality of learning materials. Therefore, this current study was aimed at investigating the use of the TG-BLL model to improve students’ speaking and listening skills viewed from their creativity at secondary schools at Algeria. To attain the research goal, this study employed quasi experimental research with using pre-test post-test control group design. 69 students were involved in this study as research samples. The samples were divided into two groups which are experimental and control groups. The samples were selected using cluster random sampling. The variable of creativity in this study was pointed as a helping variable to see whether the level of students’ creativity come to affect students’ speaking and listening skills. To see the significant effect of team games-based language learning on speaking and listening skills, the researcher applied t-test statistical analysis. Meanwhile, ANOVA statistical analysis was applied to see the interaction between the TG-BLL model and students’ creativity level on speaking and listening skills at the secondary level. The result showed that the TG-BLL model had good effect on speaking and listening skills in the experimental group. It was proven that the score of the t-test was higher than t-table with 0.05 significant level. Moreover, there was good interaction between the GBLL model and students’ creativity level to affect students’ speaking and listening skills at secondary schools. The implementation of the TG-BLL model was useful in improving students’ pronunciation, grammar, and knowledge of how sounds get reduced.